An exposition of transfer pricing motives, strategies and their implementation in tax avoidance by MNEs in developing countries - Favourate Sebele-Mpofu; Eukeria Mashiri; Samantha Chantelle Schwartz (Cogent Business & Management, 2021)
The abuse of transfer pricing by multinational enterprises (MNEs) is a topical issue the world over. Abusive transfer pricing results in the erosion of tax bases and profit shifting from countries with high tax rates to those with lower tax rates, thus enabling tax avoidance and evasion. Developing countries are argued to suffer most under the negative impacts of transfer pricing manipulation. This study investigates the strategies employed by MNEs to minimise their tax burden in developing countries. An understanding of the motives and strategies is fundamental in tax policy crafting and improvements that effectively respond to transfer pricing. Adopting the interpretivist research philosophy with the use of in-depth interviews with tax officers, tax consultants and Ministry of Finance Officials, the study established that amongst the transfer pricing schemes used by MNEs in Zimbabwe, the predominant one was the use of service fees. The most notable being management fees, this was a contribution to knowledge as this strategy was found to be scarcely discussed in literature and there was very little empirical evidence to back its existence. The study recommended use of targeted approaches by the revenue authority to minimise revenue losses through intragroup services. The findings serve as vital information for policymakers, revenue authorities and tax auditors.
Keywords: 650; Transfer pricing strategies; MNEs; Base Erosion; Profit Shifting; Tax avoidance; Developing Countries